Spatial variability of ice drift on the northeastern shelf of Sakhalin - Vyacheslav A. Dubina; Vladimir V. Plotnikov; Nadezhda M. Vakul’Skaya (Известия ТИНРО, 2015)
Spatial heterogeneity of the sea ice drift is investigated for the northeastern shelf of Sakhalin around Veninsky and Kirinsky oil fields on the data of speсtroradiometers MODIS mounted on the satellites Terra and Aqua obtained in January-May, 2015. The ice drift is calculated for the time intervals of 105 min and one day. For the former case, its velocity was evaluated as 0.2-0.4 m/s (max 1.0 m/s, registered in 2.5 km from the coast of the Nabil Bay on May 22) that is twice faster than the values for daily intervals. All possible directions of the drift were observed, with the highest frequency of the southern ones. The drift wasn’t spatially uniform by its direction in conditions of weak, unstable winds.